Investigating the microrheology of the vitreous humor using an optically trapped local probe - Watts, Fiona; Tan, Lay Ean; Wilson, Clive G.; Girkin, John M.; Tassieri, Manlio; Wright, Amanda J. (IOP Publishing, 2013)
We demonstrate that an optically trapped silica bead can be used as a local probe to measure the micro-rheology of the vitreous humor. The Brownian motion of the bead was observed using a fast camera and the micro-rheology determined by analysis of the time-dependent mean-square displacement of the bead. We observed regions of the vitreous that showed different degrees of viscoelasticity, along with the homogeneous and inhomogeneous nature of different regions. The motivation behind this study is to understand the vitreous structure, in particular changes due to aging, allowing more confident prediction of pharmaceutical drug behavior and delivery within the vitreous humor.